2019
DOI: 10.3390/cancers11091373
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Differentiating Effect of the Poly(ADP-Ribose) Polymerase Inhibitor Olaparib in Myelodysplastic Syndromes

Abstract: Myelodysplastic syndromes (MDS) are highly heterogeneous myeloid diseases, characterized by frequent genetic/chromosomal aberrations. Olaparib is a potent, orally bioavailable poly(ADP-ribose) polymerase 1 (PARP1) inhibitor with acceptable toxicity profile, designed as targeted therapy for DNA repair defective tumors. Here, we investigated olaparib activity in primary cultures of bone marrow mononuclear cells collected from patients with MDS (n = 28). A single treatment with olaparib induced cytotoxic effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Chemotherapy also carries a several‐fold increased risk of tMN, especially in younger patients 29 . There were concerns over a 0.8–2% risk of tMN in previous olaparib OC trials 29 and, in vitro , olaparib induced apoptosis of myeloid cells 30 . An increased risk of tMN versus placebo was not reproduced in SOLO2 and other recent PARP inhibitor trials, suggesting that the previous incidences might have been attributable to prior cytotoxic treatment(s) 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy also carries a several‐fold increased risk of tMN, especially in younger patients 29 . There were concerns over a 0.8–2% risk of tMN in previous olaparib OC trials 29 and, in vitro , olaparib induced apoptosis of myeloid cells 30 . An increased risk of tMN versus placebo was not reproduced in SOLO2 and other recent PARP inhibitor trials, suggesting that the previous incidences might have been attributable to prior cytotoxic treatment(s) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…There were concerns over a 0.8–2% risk of tMN in previous olaparib OC trials 29 and, in vitro , olaparib induced apoptosis of myeloid cells 30 . An increased risk of tMN versus placebo was not reproduced in SOLO2 and other recent PARP inhibitor trials, suggesting that the previous incidences might have been attributable to prior cytotoxic treatment(s) 30 . In terms of BRCA mutation status, whereas an in vitro study suggested that impaired DNA homologous recombination repair mechanisms in BRCA ‐mutated cell lines may increase the efficacy of olaparib + chemotherapy combination treatment 31 ; the effect on toxicity has yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PARP inhibitors can also be considered as guardians of stem cell reservoirs. In the culture of primary bone marrow mononuclear cells collected from patients with myelodysplastic syndromes, olaparib revealed toxicity against myeloid cells, causing a significant reduction of blasts and promyelocytes, but increased the number of metamyelocytes and mature granulocytes by promoting a dose-dependent increase of PU.1 and CEBPA transcription factors, which drive the differentiation of granulocytes and monocytes [ 137 ]. In line with these findings is another set of data from the culture of BCR‒ABL1 -positive HSC, which lost repopulation activity upon PARP inhibition [ 138 ].…”
Section: Parp1 Inhibitors In the Intentional Modulation Of Monocytmentioning
confidence: 99%
“…Combining veliparib and busulfan enhances cell death in primary MF patient samples ex vivo, and in a JAK2V617F MPN-AML xenotransplant model in vivo [ 93 ], thus demonstrating that inherent resistance to PARPi does not prevent PARPi from sensitising these cells to other anti-cancer drugs. Additionally, combining olaparib and decitabine or olaparib/talazoparib and ruxolitinib and/or hydroxyurea increases cell death compared to either agent alone [ 94 , 95 ].…”
Section: Parp Inhibitors As a Potential Treatment For Haematological Malignanciesmentioning
confidence: 99%